Medieval Scrolls Digital Archive : A comprehensive Resource for scrolls in the Middle Ages - Harvard Medical Library (2023)
"This site contains information on, links to, and bibliography for all known Western literary scrolls. This online resource will be updated regularly, and provides a single source of comprehensive information about scrolls in the Middle Ages. The database provided here contains a comprehensive list of Medieval scrolls, which generally are mentioned only occasionally or in passing, in discussions of the history of the book, or in references to scroll format when it is used for a particular type of text." [self-description]